Scenography Workshop: Learning-teaching in a time of pandemic (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The present work reflects on questions, concerns and teaching strategies revealed during the experience of remote emergency education, caused by the global pandemic of COVID-19, in the Stage Design II discipline, which is part of the curriculum of the Scenography Department of the School of Theater at the Federal University of the State of Rio de Janeiro. In such challenging times, art, with all its power, enabled a dialogic movement and collective construction, strengthening bonds, listening, creation and invention. After all, what can gestures, often minimal, of attention to singularities and differences do? What can a learning relationship that is open to encounters do? What can such encounters do?
Keywords: Pandemic; Remote teaching; Performing arts; Scenography